Language use between shop attendants and customers at a photo shop - Kimberley, Lau Yih Long (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study investigated language use between shop attendants and customers at a photo shop. The objectives were to identify languages commonly used for interaction in a smaller provision shop, to examine the responses to the uncommon language choice including how inappropriate language choices are repaired, to identify the generic structure of the photo transactions and analyze the language features in the transactions. This is a case study which was carried out at a photo shop in Sibu.The techniques used for data collection were participant observation, video recording and semi-structured interview. The participants involved were the shop attendants, the researcher and customers.A total number of 150 transactions were recorded.The results showed that Bahasa Melayu, Bahasa Pasar, Foochow, Mandarin, Hokkien and English were the common languages used in the photo transaction.There were two uncommon language choices which occurred because of the wrong judgment of the customers’ ethnicity and the responses were pausing for a while, without giving any response, shaking her head and looked at her husband and respondingto the question in Bahasa Pasar. The repair made were code switching to the language preferred by the customer- Bahasa Pasar. The generic structure of the photo transactions were analyzed based on the generic structure of service encounters found by Hasan (1985). The transactions were divided into four categories : Wait, Pick up, Drop off and no transactions and the stages identified were Sale Initiation (SI), Sale Request (SR), Sale Compliance (SC), Sale Enquiry (SE), Sale Confirmation (SC), Sale (S), Purchase (P), Purchase Closure (PC) and Finis (F). The results showed that the generic structure of photo transaction resembled Hasan’s (1985), except the additional of the Sale Confirmation (SF) stage, the Purchase (P) stage was done non-verbally and Purchase Closure (PC) was optional in the transactions. The findings have implications on cross -cultural communication and English for Specific Purposes courses and are applicable to the transactions in Asian context.